0D + 1D = 1D Zn-orotate-Bimb polyrotaxane coordination polymer: Synthesis, structure, thermogravimetric and variable temperature luminescence analysis. (15th March 2022) - Somnath,; Ahmad, Musheer; Ahmad Siddiqui, Kafeel
Graphical abstract: We have reported a novel mixed ligand 0D+1D=1D Zn-polyrotaxane coordination polymer. The thermogravimetric analysis reveals the degradation of polymer at high temperature (527 °C to 800 °C). The vary temperature luminescence study of (1) shows excellent strong luminescence in the range of 363–439 nm (2.82–3.41 eV) with slight contrast in physical appearance. Highlights: We report first example of 0D + 1D = 1D Zn-polyrotaxane coordination polymer [Zn(Or)(Bimb)(H2 O)]2 ·6H2 On (1) based on orotate/mixed ligand. The thermogravimetric analysis reveals the degradation of polymer at high temperature (527 °C to 800 °C). The vary temperature luminescence study of (1) shows excellent strong luminescence in the range of 363–439 nm (2.82–3.41 eV) with slight contrast in physical appearance. Abstract: A new polyrotaxane coordination polymer [Zn(Or)(Bimb)(H2 O)]2 ·6H2 On (1) has been synthesized using Zn(II) ion with 1, 4-bis[(1H-imidazol-1-yl)methyl]benzene) (Bimb) and potassium orotate (OrK) ligands at ambient temperature. Single-crystal X-ray diffraction, elemental analysis, variable temperature Powder X-ray diffraction (VT-PXRD), variable temperature FTIR (VT-FTIR) and TG/DT/TDG were used to characterize the complex. Complex (1) contains 0D binuclear Zn(1)–based molecular "loop", 1D Zn(2)–based molecular "string" yielding to 0D + 1D = 1D polyrotaxane coordination polymers. Supramolecular network in complex (1) is stabilized by classical strong NH∙∙∙O and OH∙∙∙O hydrogen bonds resulting in the formation of 2D inter-layer polyrotaxane coordination polymers and 3D supramolecular network via these non-covalent interactions. The solid-state variable temperature-luminescence studies of as synthesized and heated forms of (1) emit strong luminescence in the range of 363–439 nm (2.82–3.41 eV) with slight contrast in physical façade. The thermal breakdown of (1) yielded spherical shaped ZnO nanoparticles with diameters of ̴ 32 nm, as confirmed by FESEM, EDAX.